Mathematics and Mathematics Education Values: An Analysis of Implementability in Mathematics Learning at Madrasah - Pardi, M. Habib Husnial; Alkusaeri, Alkusaeri (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
Integrating values into all aspects of the learning process for a particular subject is an important part of education. Students must not only develop cognitively, but the formation of attitudes and characters must also be in line with the overall educational goals. Mathematics, as one of the core subjects that students must learn, must also reflect the values embedded in it. The success of mathematics education can be assessed through the values conveyed during the learning process. This study aims to explore and analyze teachers' understanding of Mathematical Values and Values in Mathematics Education, as well as how these values are conveyed in the classroom. This study aims to explore and analyze teachers' understanding of Mathematical Values and Values in Mathematics Education, as well as how these values are conveyed in the classroom. This study uses a qualitative approach with a case study design. Data were collected through interview techniques from 4 mathematics teacher informants determined by percussive sampling techniques. Data analysis uses an intractic model in line with the data collection process through three activities simultaneously; (1) data condensation; (2) data display, and (3) drawing conclusions/verification. The results of the study indicate that teachers' understanding of Mathematics values [rational values] and Mathematics education values are very important in improving students' logical thinking skills, and providing a comprehensive understanding of mathematics in developing their problem-solving skills. In mathematics teaching practices, teachers convey mathematical values during problem-solving activities, where students must understand various mathematical equations, concepts, and methods. While Mathematics education values (MEV) are conveyed during the problem-solving phase and reinforced at the end of the teaching and learning activities.